Fishery Stock Assessments in the Min River Estuary and Its Adjacent Waters in Southern China Using the Length-Based Bayesian Estimation (LBB) Method - Zhang, Lan-lan; Ren, Qing-qiang; Liu, Min; Xu, Qing; Kang, Bin; Jiang, Xiao-bin (Frontiers in Marine Science, 2020)
The Min River Estuary and its adjacent waters, connecting to the East China Sea, is one of the most important fishing grounds in Fujian Province, southern China; however, the stock assessments have not yet been conducted. In the present study, the length-based Bayesian estimation (LBB) method was applied for the first time to assess 20 fishery single-species stocks in the region. Catches of 8 fishes from the Class Actinopterygii and 12 shrimps from the Class Malacostraca were obtained from two commercial demersal trawlers, operated in the Min River Estuary and its adjacent waters in February, May, August and November of 2017 and 2018, covering all four seasons. The results showed that 8 species were overexploited with the estimated B/BMSY (i.e., the current exploited biomass relative to the biomass producing the maximum sustainable yield) < 0.8 (range from 0.26 to 0.71). Three overexploited fish species (the Gray’s grenadier anchovy Coilia grayii, the big head croaker Collichthys lucidus and the Trevavas croaker Johnius trewavasae) are commercially important food species in the region. All 4 overexploited shrimp species (the shrimp Parapenaeopsis cultrirostris, the Japanese snapping shrimp Alpehus japonicus, the Caridean shrimps Palaemon annandalei and P. carinicouda) are small-sized and have low commercial value. The three-lined tongue sole Cynoglossus abbreviates, a commercially important species, was classified as fully exploited status (0.8  B/BMSY  1.2). The Osbeck’s grenadier anchovy Coilia mystus and the Japanese mantis shrimp Oratosquilla oratoria, both commercially important food species in the region, were under non-fully exploited status (B/BMSY > 1.2). The results revealed that some commercially important food fishes are overexploited in the region, and small-sized, non-commercial food species can also be overexploited. There is an urgent need for local and national fisheries authorities to focus on coastal fishery management.